Dental Students' Use of Student‐Managed Google Docs and Other Technologies in Collaborative Learning. Issue 4 (1st April 2019) - Roberts, Bradley S.; Roberts, Eugenia P.; Reynolds, Steven; Stein, Amy F.
Abstract : Textbooks, once the standard of education, now have competition when students prefer the Internet and digital technology. The aim of this research study was to survey dental students at one dental school about their use of student‐managed Google Docs and other online technologies in collaborative e‐learning. All dental students in all four classes at Midwestern University College of Dental Medicine‐Arizona were invited to participate in online surveys in 2015 and 2017. The average class size was 140 (n=560 for all four years) for each survey. The 2015 survey focused on the emerging use of Google Docs in collaborative learning. The 2017 study asked not only about Google Docs but how students were using other e‐learning technologies and textbooks. In 2015, 282 students responded, for a 50.4% response rate; in 2017, 129 students responded, for a 23% response rate. The 2017 survey showed a 36% increase (p<0.0001) in the use of Google Docs in all dental classes over use in 2015, and a 67% increase (p<0.0001) in respondents' reporting they had used Google Docs during their undergraduate education. Google Docs, Blackboard, and collaboration with peers were the most popular study choices in 2017. The results showed a decline in respondents' reported use of hard copy textbooks from 24.5% in 2015 to 14.8% in 2017 (p=0.0405). Future studies are needed to increase dental educators' understanding of the ways their students are using collaborative technologies in learning and to define ways to overcome challenges posed by these technologies identified in our study.